Manajemen Pengembangan Budaya Sekolah Unggul (Studi Kasus di SMP Tamansiswa Pematangsiantar) - Junita Siahaan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
The purpose of this study was to determine the management of superior school culture development at SMP Tamansiswa Pematangsiantar. Discipline culture is manifested by various actions or coaching as well as the accuracy of teaching hours and uniforms worn. The role of all components in supporting and growing school excellence for the better. The developing culture in schools should be improved so that the learning and education process runs optimally. In addition, the need to preserve the culture and values that have been built in schools. By building commitment, experiencing programs, and activities that are supported by the school community. This research method is a qualitative development with the type of case study research. The research begins with assumptions and the use of an interpretive framework about the research problem. With the meaning imposed by individuals or groups on a social problem. Because there is a problem that is not easy to measure or listen to vague information that needs to be explored.